Tradisi Iwadh Pada Masyarakat Kampung Arab di Manado (The Tradition of Iwadh in the Kampung Arab Communities in Manado) - Hasyim Sofyan Lahilote (Institut Agama Islam Negeri (IAIN) Manado, 2021)
ABSTRACT This article examines the iwadh tradition, which is a hereditary custom practiced after the month of Ramadan and has become one of the characteristics of the Kampung Arab community that distinguishes it from other communities in the City of Manado. The purpose of this study is to determine the practice of the iwadh tradition and the function of practicing this tradition for the people of Kampung Arab. This research is descriptive qualitative with an empirical approach. Data collection techniques were carried out by means of observation, interviews, and documentation. The results of this study illustrate that this tradition is carried out by the people of Kampung Arab as a gathering place for fellow residents, as well as those from other villages involved in this activity, after the implementation of the Ramadan fast, and as a sign of gratitude after the implementation of fasting for one month. The essence of the practicing of this tradition is to forgive each other mistakes that occur between people so that the practice of fasting carried out during the month of Ramadan is expected to be accepted by Allah SWT. In addition, it has developed into a meeting place for parents, relatives and friends who have not seen each other for a long time.Keywords: tradition, Kampung Arab, iwadh. ABSTRAKArtikel ini meneliti tentang tradisi iwadh yakni suatu kebiasaan turun-temurun yang dilakukan setelah bulan Ramadan dan telah menjadi salah satu ciri khas masyarakat Kampung Arab yang membedakan dengan komunitas masyarakat lainnya yang ada di Kota Manado. Tujuan dalam penelitian ini untuk mengetahui pelaksanaan tradisi iwadh beserta fungsi pelaksanaan tradisi ini bagi masyarakat Kampung Arab. Penelitian ini bersifat deskriptif kualitatif dengan pendekatan empiris. Teknik pengumpulan data dilakukan dengan cara observasi, wawancara, dan dokumentasi. Hasil dalam penelitian ini menggambarkan bahwa tradisi ini dilakukan oleh masyarakat Kampung Arab sebagai ajang sillaturrahmi antarsesama warga Kampung Arab, maupun warga lain yang terlibat dalam kegiatan ini, pascapelaksanaan puasa Ramadan, dan sebagai tanda syukur setelah pelaksanaan puasa selama satu bulan. Inti dari pelaksanaan tradisi ini adalah saling mengikhlaskan segala kesalahan yang terjadi antarmasyarakat sehingga amalan puasa yang dilakukan selama bulan Ramadan diharapkan dapat diterima Allah Swt. Di samping telah berkembang menjadi ajang untuk bertemu dengan saudara serta sahabat dan orang tua yang telah jauh dan lama tidak bertemu.Kata kunci: tradisi, kampung Arab, iwadh.